Thermoplastic Analysis in the Study of State Diagrams of Cryoprotective Solutions in Devitrifi cation Region - Sevastianov, Stanislav S.; Osetsky, Alexander I. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 158.